Human Resource Management Challenges Towards Human Capital Management 4.0. At Pt. Pelabuhan Indonesia (Persero) I - Utama, Hendra; Yusuf, Mohammad; Sitorus, Zulham; Ramadani, Pebri (Jurnal Fokus Manajemen, 2025)
The industrial revolution 4.0 in the modern era is essentially focused on the digitalization of information technology. This explains that the industrial revolution 4.0 in the 21st century is a digital technology revolution to create a digitalization space. The digital technology revolution is a digital technology revolution to create digitalization, with a communication technology revolution, an information technology revolution, and an internet technology revolution to create digitalization. Digitalization uses digital technology. In the era of the industrial revolution 4.0, every organization needs digitalization capabilities, and digitalization needs solutions supplied by digital technology companies. The digital technology revolution in the era of the industrial revolution 4.0 will create digitalization in human resource management techniques. Pelindo Regional I has prepared its employees to face the industrial revolution 4.0. This is shown by the role of the company that has supported the development of the industrial revolution 4.0. However, employees still need management that supports the implementation of the industrial revolution 4.0. well, and encourages companies to hold training on the use of modern technology during the industrial revolution 4.0 in maximizing the promotion of Pelindo's service products. In addition, from the results of the interview, it was also concluded that what is needed by employees besides being able to use internet technology must also understand the industrial revolution 4.0. as part of good service to Pelindo service users. In running a business engaged in the service sector in the digitalization era, a good image is needed from service users, therefore it is very important for social media such as Whatsapp, Instagram, Facebook and so on to be used to form a positive image in society. Through social media, employee contributions to Pelindo are more felt by the company.